HUBUNGAN PEMBERIAN ASI DENGAN KEJADIAN IKTERUS BAYI HIPERBILIRUBINEMIA DI RSIA PURI BUNDA DENPASAR - Sulendri Nyoman; Komang Yogi Triana Triana; Desak Putu Risna Dewi; Nyoman Sutresna (Jurnal Keperawatan Priority, 2021)
Early exclusive breastfeeding has an important role in reducing the incidence of jaundice, where jaundice is a change in the skin or other organs due to a buildup of bilirubin levels in the blood and an increase in the level of bilirubin in the blood, which is called hyperbilirubinemia. This study aimed to determine the correlation between breastfeeding and the incidence of hyperbilirubinemia infant jaundice at RSIA Puri Bunda Denpasar. This study used a case-control method, comparing the case group with the control group and a retrospective approach. The number of samples was 86 patients' medical record files. The sampling was using purposive sampling through the observation sheet and data analysis using the Chi-Square test. This study showed that exclusive breastfeeding had less incidence of jaundice (16.7% in the case and control groups) while the incidence of jaundice was higher in breastfeeding and formula milk in both the case and control groups. The results of the chi-square statistical test obtained p-value = 0.023, meaning that there was a significant correlation between breastfeeding and the incidence of jaundice in hyperbilirubinemia infants. It is recommended that the hospital be able to educate and socialize early exclusive breastfeeding to patients.